"Bases for Territory-based Rural Development: Central Region in Vietnam, Hue" - Rodero Franganillo, Adolfo (Revista de Fomento Social, 2008)
Reseña de la obra de: VAN THAT, Nguyen y THANT HA, Thai, editors (2007) Bases for Territory-based Rural Development: Central Region in Vietnam, Hue. Hue College of Economics e INSAETEA, 324 pp.